2015
DOI: 10.1111/phn.12232
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Spanish Version of the “Abuse Assessment Screen” among Pregnant Women

Abstract: The Spanish AAS has good test-retest reliability, specificity, and construct validity. The sensitivity was good for severe psychological abuse and moderate for severe physical abuse. Further formal psychometric evaluations, in other languages from countries with low prevalence of abuse, remains a priority for clinical and research efforts in pregnancy domestic violence screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Women who reported that they don’t feel safe in their relationship and those found to be depressed using the SRQ were more likely to have experienced any form of violence in the last 12 months. Our study is not the first to find a consistent relationship between IPV and depression as previous studies from Malawi 47 , 48 , 49 and elsewhere 50 have made similar observations amongst pregnant women, and more so, amongst those experiencing IPV 51 and are HIV-positive. 52 , 53 However, our study’s finding on the relationship between safety in a relationship and IPV is in contrast to an earlier study in primary care, which found that many women who reported experiencing violence in their relationship did not report feeling unsafe at home.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Women who reported that they don’t feel safe in their relationship and those found to be depressed using the SRQ were more likely to have experienced any form of violence in the last 12 months. Our study is not the first to find a consistent relationship between IPV and depression as previous studies from Malawi 47 , 48 , 49 and elsewhere 50 have made similar observations amongst pregnant women, and more so, amongst those experiencing IPV 51 and are HIV-positive. 52 , 53 However, our study’s finding on the relationship between safety in a relationship and IPV is in contrast to an earlier study in primary care, which found that many women who reported experiencing violence in their relationship did not report feeling unsafe at home.…”
Section: Discussionsupporting
confidence: 77%
“…47 In Spain, the AAS had good test-retest reliability, specificity and construct validity amongst pregnant women. 48 The self-reporting questionnaire (SRQ) was used to screen for depression. The internal consistency of the SRQ amongst Malawian women was high (Cronbach’s alpha 0.825).…”
Section: Methodsmentioning
confidence: 99%
“…This protocol for the TCCA of abuse questionnaires was based on our literature review (Alhabib et al, 2013;Antoniou et al, 2010;Burjalés-Martí et al, 2018;Cases et al, 2015;Cheung et al, 2020;Connelly et al, 2005;Escriba-Agüir et al, 2015;Fisher Step…”
Section: Results: the Protocol For The Tcca Of Abuse Questionnairesmentioning
confidence: 99%
“…While undertaking the task of translating the CAS into Brazilian Portuguese, we analyzed a wide range of translation and cross-cultural adaptation (TCCA) approaches dealing with abuse questionnaires. Some of them were very simplistic, for example, not including cognitive interviews/pilots, review by external reviewers, nor mentioning the developer's role in the process, which could raise questions about their rigor and consistency (Connelly et al, 2005;Escriba-Agüir et al, 2015;Iskandar et al, 2015;Umeda & Kawakami, 2014). Facing this dilemma, we propose a protocol for the TCCA of the CAS into Brazilian Portuguese based on meticulous practices, which could prove useful to the TCCA of other abuse questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen of the tools were originally designed in English and then translated, culturally adapted and validated in different languages such as Arabic (Haddad et al, 2011), Chinese (Tiwari et al, 2015;Tiwari et al, 2007), Spanish (Loinaz-Calvo et al, 2011;Escribà-Agüir et al, 2015;Chen et al, 2005;Garcia-Esteve et al, 2011;Fogarty & Brown, 2002;Fernández-Fuertes et al, 2006;Muñoz-Rivas et al, 2007;Torres et al, 2010;Sierra et al, 2011;Buesa & Calvete, 2011;Lopez-Ferré & Andrés-Pueyo, 2007), Greek (Antoniou et al, 2010), Indonesian (Iskandar et al, 2015), Italian (Signorelli et al, 2014) or Japanese (Umeda & Kawakami, 2014). Spanish is the main language in this review.…”
Section: Validation Languagesmentioning
confidence: 99%